2012
DOI: 10.1021/jp305774n
|View full text |Cite
|
Sign up to set email alerts
|

UV- and Visible-Light Photocatalytic Activity of Simultaneously Deposited and Doped Ag/Ag(I)-TiO2 Photocatalyst

Abstract: Ag modification has been demonstrated to be an efficient strategy to improve the photocatalytic performance of TiO2 photocatalysts. However, the previous studies about the Ag modification are only restricted to the surface loading of metallic Ag or Ag(I) doping, investigations have seldom been focused on the simultaneously deposited and doped Ag/Ag(I)-TiO2 photocatalyst. In this study, Ag/Ag(I)-TiO2 photocatalyst was prepared by a facile impregnated method in combination with a calcination process (450 °C) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
120
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(126 citation statements)
references
References 65 publications
4
120
0
2
Order By: Relevance
“…Severals tudies have shown that noble metals such as platinum, [36] gold, [37] ruthenium, [38] and silver [39] are the most efficient co-catalysts due to their large work functions.…”
Section: Hydrogen Evolution Reaction On Tmdc/tio 2 Nanocompositesmentioning
confidence: 99%
“…Severals tudies have shown that noble metals such as platinum, [36] gold, [37] ruthenium, [38] and silver [39] are the most efficient co-catalysts due to their large work functions.…”
Section: Hydrogen Evolution Reaction On Tmdc/tio 2 Nanocompositesmentioning
confidence: 99%
“…Doping is one of the means to achieve the above-mentioned characteristics. Metal ions of noble metals (Pt, Pd, Ag, and Au) [166] and transition metals (Cr, Cu, Mn, Zn, Co, Fe, and Ni) [167] are used as dopants [168]. Even non-metals such as C, N, S, and P are used for this purpose [160,161,163,169].…”
Section: Titanium Dioxide As Photocatalystsmentioning
confidence: 99%
“…In recent years, visible light responsive photocatalysts have been extensively studied. TiO 2 modified systems have been prepared to obtain visible-light reactivity in recent years [15][16][17][18]. Polyoxometalates (POMs) have also been recently studied as efficient photocatalysts for the degradation of organic dyes and it indicates that the photocatalytic activity of POMs is comparable to that of the semiconductor TiO 2 [19][20][21].…”
Section: Introductionmentioning
confidence: 99%